DOES THE PROCYCLICALITY OF CAPITAL REQUIREMENTS AFFECT FINANCIAL STABILITY IN CEMAC? - Djekonbé, Djimoudjiel; Paul, Ningaye; Daba, Nafé (International Journal of Research -GRANTHAALAYAH, 2020)
The objective of this article is to analyze the effects of procyclical variations of the capital requirements for risk coverage on financial stability in the CEMAC[1]. In order to achieve this objective, we have specified and estimated a panel VAR model using the structural factorization method on quarterly Central Bank data over the period 2006-2017. Firstly, the results show that procyclical capital adjustments in the CEMAC region lead to short-term financial instability through the contraction of credit to the private sector. Secondly, despite the low level of financial development, the effects maintained by the adjustment of monetary policy instruments in the short term remain significant on price stability. Finally, in the long term, the procyclicality of regulatory capital makes it possible to revive economic activity and guarantee financial stability. These results lead us to recommend the adoption of a more discretionary monetary policy so as to make more procyclical the capital requirement. [1] Economic Community of Central African States comprising Cameroon, Central African Republic, Chad, Congo, Gabon and Equatorial Guinea.